Ginger vodka: ethanol production using Ginger as an antibacterial. - BHARATI K. THOSARE (International Journal of Pharma and Bio Sciences, 2016)
Ethanol is one of the efficient energy sources that can be produced by using any agricultural product like grains, straws, fruits etc. Ethanol like vodka can be distilled from virtually any fermentable ingredients. Ginger (Zingiber officinale) has long been used as naturopathy due to their potential antimicrobial activity against different micro-organisms. Maize is relatively inexpensive compared with other feed stock and grains. However, before ethanol fermentation pretreatment is needed so we liquefied and saccharified the sprouted maize for conversion of starch into fermentable sugars. The fermentation of maize was conducted by Saccharomyces cerevisiae under aerobic condition with optimum shaking of broth. The novelty of this experiment is use of ginger extract for its antimicrobial activity which decreases the impurities in product and worked as enhancer for alcohol production. The gas chromatographic estimation has confirmed that the presence of ginger extract increased the quantity as well as quality of ethanol.